HUMAN AND MATERIAL RESOURCES AS CORRELATES OF ACADEMIC PERFORMANCE OF PRIVATE AND PUBLIC SECONDARY SCHOOL STUDENTS IN ONDO STATE, NIGERIA - Timilehin, Ekundayo Haastrup; Ogbomida, Alonge Hezekiah (European Scientific Journal, ESJ, 2012)
The study examined human and material resource availability and students’ academic performance in public and private secondary schools in Ondo State. An inventory format was designed and used to collect data from a sample of 65 public and 49 private secondary schools selected through a stratified random sampling. Five hypotheses were generated and tested at 0.05 level of significance. Pearson product moment correlation and t-test statistic were used to test the hypotheses. The study showed that human and material resources were not significantly related to students’ academic performance in both public and private schools. The study also revealed that there was no significant difference in human resources availability in the two schools. It was also revealed in the study that private schools were better equipped in terms of material resources than the public schools and that private schools had better academic performance than the public schools in public examinations. It was therefore recommended that both human and material resources should be well and adequately utilised to ensure better academic performance. It was also recommended that government should live up to her responsibility of providing adequate and relevant materials to the public schools so as to ensure better academic performance of the students.